Keamanan Obat Untuk Ibu Hamil Dan Menyusui - Ilil Maidatuz Zulfa; Widya Handayani (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2022)
Pregnancy and breastfeeding are special conditions that need to be considered when taking drugs because not all drugs are safe for pregnant and breastfeeding mother. Mistakes in drug consumption can harm the fetus and baby. In the community, pregnant women and breastfeeding mothers often have difficulty in choosing symptomatic drugs available at pharmacies and drug stores due to the lack of knowledge about the safety of drugs for these conditions. Related to this, it is very important to increase public knowledge through the provision of information and tips so that people no longer have difficulty in choosing safe medicines for these conditions.